Effect of 32-Weeks High-Intensity Interval Training and Resistance Training on Delaying Sarcopenia: Focus on Endogenous Apoptosis - Su, Hao; Wen, Tianhao; Liu, Dongsen; Shao, Jia; Zhao, Lei; Gao, Qi (Frontiers in Physiology, 2022)
Sarcopenia caused by aging is an important factor leading to a decline in the quality of life of older people. Apoptosis in muscle atrophy accelerates the process of muscle loss in older populations. The present study aimed to investigate the effects of 32 weeks of high-intensity interval training (HIIT) and resistance training (RT) on the skeletal muscle-related indices and provide a theoretical basis for regulating the mitochondrial-mediated pathway to delay sarcopenia. We randomly selected 10 from eight-month-old male SD rats (N = 130) as the baseline group; after 1 week of adaptive feeding, the rats were sacrificed. The remaining rats were randomly assigned to one of three groups: control group (C, N = 40, natural aging for 32 weeks), HIIT group (H, N = 40, performed six loops of 3 min at 90% and 3 min at 50% VO2 max speed treadmill running, with 5 min at 70% VO2 max speed at the beginning and the end of the training, 3 times a week for 32 weeks), and resistance group (R, n = 40, 46 min per day, 3 days per week, with a 30% maximum load on a treadmill with a slope of 35°, 15 m/min). The soleus muscles were collected for analysis at baseline and every 8 weeks. Aging resulted in decreased soleus muscle mass and Bcl-2 levels in the mitochondria, while the levels of reactive oxygen species (ROS) and Bax did not change. HIIT reversed the age-associated activation of pro-apoptotic processes, but RT did not. In addition, when rats were aged from 8 to 16 months, the level of Cyt-C did not change, the Caspase-9 levels and Caspase-3 levels decreased gradually in the soleus muscles, the rats of both the HIIT and RT groups had these indices decreased at 32 weeks. The results suggest that the age-associated loss of muscle mass was reversed by training, and the effect of RT was better than that of HIIT. Both the HIIT and RT rats showed a decrease in the apoptosis of skeletal muscle cells after 32 weeks of intervention. HIIT performed better for long-term intervention regarding the pro-apoptotic factors. This study warranted further research to delineate the underlying mechanism of effects of different exercise methods on the changes of aging skeletal muscle at in vivo level.